Treatment of vibro harveyi-infected peneaus monodon using alibutbut (Tabernaemontana pandacaqui Poir) plant powder. - Bacaling, Marivic Tabalina
The cytotoxicity test of crude methanolic leaf extract using Brine Shrimp Lethality Asssay revealed that Alibutbut (Tabernaemontana pandacaqui Poir.) is safe to use in treating vibrio-infected penaeid shrimps., The effectiveness of the alibutbut powder against vibriosis was examined through the determination of the post-larvae 20 (PL 20) penaeid shrimp mortality and the water microbial assay after 48 hours. Percent penaied shrimp mortality (0-6.67 percent) and microbial count (2.91 x 10 raise to the 4th power - 3.26 x 10 raise to the 4th power cfu/mL) of the plant treatments were significantly lower compared to the negative control (no treatment) that exhibited 50 percent penaeid shrimp mortality and a microbial count greater than 6.00 x 10 raise to the 4th power cfu/mL. NThe results of the experiment showed that Alibutbut palnt powder is indeed effective in controlling Vibrio harveyi bacteria.